Genetically diverse Plasmodium falciparum Southern Africa isolates provides insights into antimalarial drug sensitivity and gametocyte biology - Birkholtz, Lyn-Marie (University of Pretoria, 2025)
Thesis (Ph.D (Biochemistry))--University of Pretoria, 2024.